Pathological fracture as the presenting feature in pediatric osteosarcoma1. Issue 7 (31st December 2012) - Lee, Ryan K.L.; Chu, Winnie C.W.; Leung, Joyce H.Y.; Cheng, Frankie W.T.; Li, C.K.
Abstract Background Pathological fracture is an uncommon presentation in patients with long bone osteosarcoma. Procedures We retrospectively reviewed the database of all patients with histologically proven osteosarcoma under the age of 18 years from 1991 to 2011 in a tertiary pediatric oncology referral center. Five patients with pathological fractures as the first presentation of osteosarcoma were identified. The treatment strategies and complications were evaluated. Ten sex‐, age‐, and site‐ matched osteosarcoma patients without pathological fracture were selected as controls. The incidence of distant metastases and outcome, including local recurrence and survival, were compared between the index (with pathological fracture) and the control (without pathological fracture) groups. Results In the index group, all five patients were boys and the mean age of onset was 13.1 years (range 9.2–14.9). Three patients (60%, 3/5) received amputation and two (40%) had wide local excision of the tumor. Pathological fracture group showed higher rate of lung (60% vs. 10%, P = 0.04) and bone (60% vs. 10%, P = 0.04) metastases at presentation, and shorter overall 5‐year survival (P = 0.04) than the control group. There was no significant difference of local recurrence (20%, P = 1.00) between these two groups regardless of the type of operation. Conclusion Osteosarcoma complicated by pathological fracture as first presentation had higher incidence of lung and bone metastases at presentation and worse survival rate when compared with patients without pathological fracture. Pediatr Blood Cancer 2013; 60: 1118–1121. © 2012 Wiley Periodicals, Inc.